2021
DOI: 10.1071/an20297
|View full text |Cite
|
Sign up to set email alerts
|

Formulating diets based on whole cassava tuber (

Abstract: Context Formulating rations with high energy and protein feeds such as cassava tuber and gliricidia, is an important strategy to increase liveweight gain (LWG) of bulls and improve profitability of smallholder farmers in Indonesia. Aims Two on-farm experiments were conducted to evaluate the effect of increasing the supplementation level of a mixture of cassava (Manihot esculenta) whole root tuber powder and fresh gliricidia (Gliricidia sepium) on feed intake and LWG of Ongole and Bali bulls given fresh corn s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 20 publications
1
8
2
Order By: Relevance
“…The ADG of Ongole bulls maintained under the CFS was 0.31 kg/head with feed intake of 1.8% LW/day (Table 3). These ADG and intake values are similar to those reported by Wiyatna et al (2012) in a very similar production system with Ongole bulls (ADG of 0.25 kg/head with a feed intake of 1.3% LW/day) and Marsetyo et al (2021) with fresh corn stover (0.31 kg/head). Supplementation increased the ADG to 0.60-0.75 kg/head (Table 3), which Table 3.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The ADG of Ongole bulls maintained under the CFS was 0.31 kg/head with feed intake of 1.8% LW/day (Table 3). These ADG and intake values are similar to those reported by Wiyatna et al (2012) in a very similar production system with Ongole bulls (ADG of 0.25 kg/head with a feed intake of 1.3% LW/day) and Marsetyo et al (2021) with fresh corn stover (0.31 kg/head). Supplementation increased the ADG to 0.60-0.75 kg/head (Table 3), which Table 3.…”
Section: Discussionsupporting
confidence: 90%
“…The feed intake in supplemented treatments (R 1 , R 2 and R 3 ) ranged from 5.58 to 6.29 kg/head per day, which was similar to Lestari et al (2011) who reported that the feed intake of Ongole bulls of similar LW, could reach 6.42 kg/ head per day. Intake in treatments R 1 , R 2 and R 3 ranged from 2.38 to 2.69% LW/day, which was lower than Marsetyo et al (2021) who recorded an intake of 3.28% LW/day in Ongole bulls supplemented with cassava powder and fresh G. sepium. Marsetyo et al (2021) offered a similar supplement at 1.6% LW/day, whereas in this experiment, concentrates were given at 1% LW/day.…”
Section: Variablecontrasting
confidence: 60%
See 1 more Smart Citation
“…When used in the form of hay, legumes can be a strategic reserve of fiber and protein for prolonged periods of drought [ 13 ]. Some of the main legumes used in the Brazilian semi-arid region are gliricidia ( Gliricidia sepium ), “catingueira” ( Caesalpinia bracteosa ), “sabiá” ( Mimosa caesalpiniifolia Benth ) and “catanduva” ( Piptadenia moniliformis Benth ), due to important characteristics for animal production such as perenniality, high crude protein content (>16%) and average ruminal dry matter degradability of 50–60% [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the highest level of supplement, the bulls required less feed/kg LWG. Our results were within the range reported in the previous studies in Ongole crossbred bulls offered cassava tuber and Gliricidia sp., the FCR was 18 kg feed DM/kg LWG (Marsetyo et al 2021) and in Ongole crossbred bulls fed elephant grass adlibitum, the FCR was 24 kg feed DM/kg LWG (Antari et al 2016).…”
Section: Intakes Liveweight Gain Hip Height Gain and Body Condition S...mentioning
confidence: 99%